Pemberdayaan Perempuan di Bidang Pertanian dalam Meningkatkan Kesejahteraan Keluarga pada Kelompok Wanita Tani - hilmansyah, muhammad; Cahyani, Indri; Adryant, Haris Rasyad; Yulianti, Revina; Khairunnisa, Rizka; Hamdan, Ahmad (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
Abstract. Increasing the productivity of women's workforce has a strategic role and potential to support the growth and development of household income. That way women farmers have the responsibility for the stability and survival of the family. The purpose of this study is 1) To determine the participation of KWT Mawar Bodas members. 2) To find out the skills of KWT Mawar Bodas in processing agricultural products. 3) To find out the role of women's empowerment in improving family welfare at KWT Mawar Bodas. This study uses a qualitative research method, with a case study approach. Data collection techniques used are Observation, Interview, and Documentation. The results of this study indicate that in improving family welfare, KWT Mawar Bodas seeks to provide information regarding the benefits produced, as well as strives to develop, preserve its agricultural land properly and innovate, and utilize agricultural products innovatively by marketing agricultural products in the form of vegetables, processed cystic spinach and vegetable chips through the Thursday Market and through social media.